2008
DOI: 10.1177/1559827608323213.
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Men's Health and Masculinity

Abstract: How men seek help and use health care services are important components of their physical and mental health. Abstract: Men's health is a new and evolving area of specialty that goes beyond men's cancers and sexual activities. Men's health in the 21st century incorporates a broader conceptualization of health, health behaviors, and lifestyle choices. This new focus results from the fact that men continue to lag behind women in life expectancy and in health care use, a situation that is worse for minority men. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 63 publications
2
52
0
Order By: Relevance
“…, Garfield et al . ). Our findings are consistent with previous studies on men's health that support community and workplace health services with flexible schedules (evening and weekends) and advocate for integrated health care services (Robertson et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…, Garfield et al . ). Our findings are consistent with previous studies on men's health that support community and workplace health services with flexible schedules (evening and weekends) and advocate for integrated health care services (Robertson et al .…”
Section: Resultsmentioning
confidence: 97%
“…Health disparities between men and women have been explained by biological and social determinants, and, with no single explanation for all causes of death, gender norms and gender socialisation are considered major contributing factors (Garfield et al . ). In a position paper on men's health promotion, Robertson et al .…”
Section: Introductionmentioning
confidence: 97%
“…The task of engaging men in counseling is difficult considering college men's reluctance to seek help and their propensity to hold negative attitudes about mental health services (Groeschel, Wester, & Sedivy, 2010). As a result, novel approaches emphasize "male-friendly" language and practices, reframing counseling as "consultation" and a "team effort," and focusing on men's strengths instead of deficits (Brooks, 2010;Garfield, Isacco, & Rogers, 2008;Isacco, Talovic, Chromik, & Yallum, Shen-Miller et al 2013;Kiselica & Englar-Carlson, 2010;Kiselica et al, 2008). These scholars have made important inroads into the treatment of men, yet their focus remains largely on the individual.…”
Section: Integrating the Ecological Model With The Mcamentioning
confidence: 99%
“…(Vogel et al, 2006) as well as qualitative research on men's narratives regarding help-seeking behaviors for psychological concerns (Mahalik, Good, & Englar-Carlson, 2003 Control subscales. Socioeconomic status has been documented as a key construct in epidemiological research on men's help-seeking for psychological and physical concerns (Garfield et al, 2008). Given the connection between SES and concrete barriers to accessing care, this result can likely best be conceptualized within the Health Belief Model.…”
Section: Primary Analysesmentioning
confidence: 99%
“…With regards to eating habits, men have been shown to engage in less healthy diet and nutrition practices across their lifespan ranging from college-aged students (Davy, Benes, & Driskell, 2006) to the elderly (Baker & Wardle, 2003). Garfield, Isacco, and Rogers (2008), in their review of men's health and masculinity, reported that men who endorse more traditional masculine ideologies tend to (a) eat larger portions, (b) be inattentive to nutritional labels, (c) ignore nutritional information when making food choices, (d) not eat as much of foods that are identified as healthy (e.g., fruits and vegetables), and (e) focus on proteins and vitamins instead of fat and calories. When we consider mainstream media sources, fast food and frozen food companies have marketed "man-sized meals," indicating that larger-than-life food portions are considered more appropriate for their male customers than smaller portions or healthier options.…”
Section: What Specific Behaviors Place Men At Risk For Health Problems?mentioning
confidence: 99%